Determination of Doxycycline Hyclate by Batch and Reverse Flow Injection Analysis Based on the Oxidative Coupling Reaction with 3-Methyl-2-benzothiazolinone Hydrazone hydrochloride (MBTH) (Baghdad Science Journal, 2016)
New, simple and sensitive batch and reverse FIA spectrophotometric methods for the determination of doxycycline hyclate in pure form and in pharmaceutical preparations were proposed. These methods based on oxidative coupling reaction between doxycycline hyclate and 3-methylbenzothiazolinone-2-hydrazone hydrochloride (MBTH) in the presence ammonium ceric sulfate in acidic medium, to form green water-soluble dye that is stable and has a maximum absorbance at 626 nm. A calibration graph shows that a Beer's law is obeyed over the concentration range of 1-80 and 0.5-110 ?g.mL-1 of DCH for the batch and rFIA respectively with detection limit of 0.325 ?g.mL-1 of DCH for r-FIA methods. All different chemicals and physical experimental parameters affecting the development and stability of the colored product were carefully studied. The proposed methods were successfully applied for the determination of DCH in pharmaceutical preparations.